أثر استخدام منوذج ويتلي في مادة الكيمياء على مهارات عمليات العلم والتحصيل الدراسي لدى طالبات الصف احلادي عشر في سلطنة عمان - Ajmi Sakina Hassan Hamed
This study aims to investigate the effects of using the Wheatley model on the achievement and learning processes among eleventh-grade students in Chemistry in the Sultanate of Oman. This study used the quasi-experimental quantitative approach. An experimental design called the “Solomon four group design” was used. The study sample consisted of 114 students, who were divided into an experimental group and three control groups. The experimental group was taught based on the Wheatley model, while the control groups were taught using the traditional way. The study tools involved two scales: the Science Process Scales which consist of (32) items. The Science Process Scales also comprise basic science skills, prediction, deduction, and the use of numbers. The Science Process Scales further include the chemistry achievement tests which consist of (30) paragraphs, and the Bloom’s cognitive levels which include: remembering, understanding, applying, and analysing. The researcher prepared both the teacher's and the student’s guide according to the Wheatley model. She also calculated the reliability coefficient for each of the research tools using the Cronbach alpha coefficient for internal consistency which yielded (0.76). The Pearson correlation coefficient was also calculated for the science operations scale and yielded (r) = (0.64). The study discovered the statistically significant differences at the level of significance (α ≤0.05) between the mean scores of the experimental group and the mean scores of the control groups in the scale of the total science processes and the overall achievement test in favour of the experimental group. In light of these findings, a number of recommendations are made, including: the necessity for in-service teacher training programmes to incorporate teaching models stemming from the constructivist theory such as the Wheatley model. One of the recommendations is that the teaching plans for chemistry and science teachers to include teaching models that take into account the development of students' science operations skills.